Protein kinase D exerts neuroprotective functions during oxidative stress via nuclear factor kappa B‐independent signaling pathways. Issue 6 (31st August 2017) - Liliom, Hanna; Tárnok, Krisztián; Ábrahám, Zsófia; Rácz, Bence; Hausser, Angelika; Schlett, Katalin
Abstract: Members of the protein kinase D (PKD) family of serine/threonine kinases are known to exert diverse roles in neuronal stress responses. Here, we show the transient activation and nuclear translocation of endogenous PKD upon oxidative stress induced by H2 O2 treatment in primary neuronal cultures. Using pharmacological inhibition, we show that PKD activity protects neurons from oxidative stress‐induced cell death. Although members of the canonical nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF kappaB) pathway were phosphorylated upon H2 O2 treatment, it was found that the neuronal response to oxidative stress is not executed through the nuclear translocation and activity of RelA. On the other hand, we demonstrate for the first time in neuronal cells, the association of green fluorescent protein‐tagged kinase inactive PKD1 with mitochondrial membranes in vivo and the presence of PKD activity in the close vicinity of mitochondria in vitro . Our findings thus support the notion that the neuroprotective role of PKD is exerted independently from NF kappaB signaling and suggest a potential mitochondrial function for PKD in cultured neurons. Abstract : We show the nuclear translocation and activation of protein kinase D (PKD) upon oxidative stress in primary cortical neurons. Oxidative stress does not induce nuclear translocation and activation of NFκB (nuclear factor kappa‐light‐chain‐enhancer of activated B cells) p65. PKD‐dependent neuroprotection during oxidative stress is also exerted in an NFκB‐independent manner. PKD was shown to associate with mitochondrial membranes, where PKD activity was also detected. These results raise the possibility that PKD exerts neuroprotection via regulating mitochondrial functions and/or transcription.